2011
DOI: 10.1016/j.neuron.2011.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Different Time Courses for Learning-Related Changes in Amygdala and Orbitofrontal Cortex

Abstract: The orbitofrontal cortex (OFC) and amygdala are thought to participate in reversal learning, a process in which cue-outcome associations are switched. However, current theories disagree on whether OFC directs reversal learning in the amygdala. Here, we show that during reversal of cues' associations with rewarding and aversive outcomes, neurons that respond preferentially to stimuli predicting aversive events update more quickly in amygdala than OFC; meanwhile, OFC neurons that respond preferentially to reward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
144
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(161 citation statements)
references
References 59 publications
14
144
2
1
Order By: Relevance
“…In monkeys and rats, amygdala lesions impair reward-related and affective behavior (3,4). Individual amygdala neurons respond to basic rewarding and aversive stimuli (5,6), code expectations about rewarding and aversive outcomes (7)(8)(9)(10), and update the positive and negative values of conditioned stimuli during learning (9)(10)(11). In human imaging studies, amygdala activation is associated with basic rewards (12), decision variables (13), and decision-related emotions (14).…”
mentioning
confidence: 99%
“…In monkeys and rats, amygdala lesions impair reward-related and affective behavior (3,4). Individual amygdala neurons respond to basic rewarding and aversive stimuli (5,6), code expectations about rewarding and aversive outcomes (7)(8)(9)(10), and update the positive and negative values of conditioned stimuli during learning (9)(10)(11). In human imaging studies, amygdala activation is associated with basic rewards (12), decision variables (13), and decision-related emotions (14).…”
mentioning
confidence: 99%
“…However, some findings conflict with this model. For example, while some BLA neurons differentially fire for rewarding or aversive reinforcers, many respond to both, suggesting that BLA neurons receive information about both positive and negative stimuli (Schoenbaum et al 1999;Paton et al 2006;Morrison et al 2011). These data suggest that a certain degree of segregation of neurons encoding positive versus negative valence is likely, but it does not exclude the possibility that the neurons responding to both valences may also have valence-specific roles and/or contribute to arousal or attentional processes.…”
Section: Models For Segregated Function In the Blamentioning
confidence: 94%
“…In this case, valence segregation may not be a predetermined or hardwired property of individual neurons, but rather arises from the experience or history of the animal. Nevertheless, experimental data showing that mostly segregated populations of amygdala neurons respond to appetitive or aversive stimuli provides support for Models 1 and 3 (Schoenbaum et al 1999;Paton et al 2006;Morrison et al 2011). In agreement with classical amygdala studies showing that aversive learning is mediated by the convergence of the unconditioned and conditioned stimuli within single BLA neurons (Barot et al 2008;Chung et al 2011), a recent study found that cells in the amygdala that encode an unconditioned stimulus of opposite valence (and different sensory modality) significantly contributes to both Pavlovian and instrumental associative learning and conditioned responses acquired after learning (Gore et al 2015a,b).…”
Section: Models For Segregated Function In the Blamentioning
confidence: 96%
See 2 more Smart Citations